2012
DOI: 10.1155/2012/457173
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Early Childhood Risk Factors for Overweight and Obesity among Low-Income Predominantly Black Children at Age Five Years: A Prospective Cohort Study

Abstract: Objective. To identify maternal and early childhood risk factors for obesity and overweight among children at age 5 in the state of Alabama. Methods. We recruited 740 mothers during early pregnancy from University of Alabama Prenatal Clinics in a prospective cohort study and followed them throughout pregnancy. We followed their children from birth until 5 years of age. The main outcome measure was obesity (BMI for age and sex ≥ 95th percentile) at 5 years of age. We used poisson regression with robust variance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 63 publications
2
46
2
5
Order By: Relevance
“…These studies found an association between maternal prenatal smoking and childhood obesity even after accounting for various confounding factors. 12,16,76,[78][79][80][81][82][83][84][85][86][87][88][89][90][91] Although there is a compelling link between prenatal smoking and childhood obesity, it is not always clear-cut for both genders and all maternal smoking levels. 86,87 One study followed children from 2 to 10 years of age and found that males whose mothers smoked during pregnancy had a lower BMI at age 2 years than those born to non-smoking mothers or had partners who smoked.…”
Section: Sleepmentioning
confidence: 99%
“…These studies found an association between maternal prenatal smoking and childhood obesity even after accounting for various confounding factors. 12,16,76,[78][79][80][81][82][83][84][85][86][87][88][89][90][91] Although there is a compelling link between prenatal smoking and childhood obesity, it is not always clear-cut for both genders and all maternal smoking levels. 86,87 One study followed children from 2 to 10 years of age and found that males whose mothers smoked during pregnancy had a lower BMI at age 2 years than those born to non-smoking mothers or had partners who smoked.…”
Section: Sleepmentioning
confidence: 99%
“…for these factors, MTS remains an independent risk factor for childhood obesity (2,7,8,17,18). The independent risk of obesity with maternal smoking suggests that MTS programs altered adipocyte physiology, leading to increased adiposity in the progeny.…”
Section: Mts Increased Vat In Male Ratsmentioning
confidence: 99%
“…Neonatal rat cotinine levels fell well within the range of 200 to 800 ng/ml, indicating an "active smoker" according to ARUP laboratories. Not only does MTS predispose the fetus to IUGR, but it also increases the risk of obesity in childhood (2,7,8,17,18). Certainly, social factors interplay with MTS exposure during pregnancy, such as decreased physical activity, parental education, and socioeconomic status associated with postnatal cigarette exposure.…”
Section: Mts Increased Vat In Male Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the association between birth weight and childhood obesity has been reported results are inconsistent [36]. Further study of the combined effects of mothers' health determinants and infant birth weight on the development of childhood obesity could be helpful in identifying risk factors and effective interventions for prevention [37,38].…”
Section: Cohortmentioning
confidence: 99%